PENGARUH SERVICE QUALITY PADA JASA CUCI MOBIL DKI JAKARTA - Patricia, Prita; Krisantono, Luvian; Darmawan, Stephen Junadi; Salim, Sutrisno (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
The aim of this research is to analyze and to understand the relation between service quality, perceived service fairness, convenient and product portfolio to customer service satisfaction. The research is also done to find out the effect of customer service satisfaction, trust, and word of mouth specifically in the car wash industry. The data is collected by using questionnaires as the survey method which analysed using Multiple Regression Analysis. The survey result shows that there are influence service quality, which are assurance, product portfolio, convenience, perceived service fairness, and reliability. The five dimensions also show the positive relation with customer service satisfaction, so does customer service satisfaction and trust to word of mouth. Based on the result of this research, gaining positive customer satisfaction and word of mouth in the car wash industry imply the need in focusing on improving service in matters concerning assurance product portfolio and convenience. This research shows that the assurance dimension has the most significant influence on customer satisfaction and the trust dimension has the most significant impact on word of mouth in the car wash industry in DKI Jakarta.